PULAU SEBATIK SEBAGAI PINTU KECIL HUBUNGAN INDONESIA-MALAYSIA - Purnawan Basundoro (Faculty of Humanities, Jember University, 2013)
Indonesia and Malaysia are two neighbouring countries that share land marine boundaries. One of the boundaries of the two countries is situated in a small island called Sebatik. The island is devided into two parts, one part is under the Indonesia’s jurisdiction and the other one is under the Malaysia’s juridiction. As a boundary island, Sebatik has a strategic role for the two countries. The friendship betwen them is very obvious because in this tiny island the citizens of the wo counties can visit each other without being bothered by complicated administrative issues and procedures. However, it is quite frequent that tensions between the two countries arise in the island where military personnels are present to guard the borders. Apart from the oftenemerging tensions between the two countries due to the political dynamics Sebatik island has played a role as a small door to build peaceful relation between Malaysia and Indonesia, as demonstrated by daily contacts among the local people. Keywords: Sebatik, Indonesia, Malaysia, diplomacy